Efforts to Grow Muslim Mahabbah in High Schools Through Islamic Religious Learning - Nurhayati, Lilis (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Teachers greatly influence students' religious development, including how Islamic religious education teachers pay attention to students in educating and growing Muslim mahabbah. Mahabbah Muslim here is defined as the love of Allah and His Messenger. Islamic Religion teachers use many ways to motivate students to carry out Islam's teachings. Therefore, the researcher wants to learn more about the teacher's efforts to grow Muslim mahabbah in SMA 2 Bandung. This research aims to describe the efforts of Islamic religious education teachers in cultivating Muslim mahabbah in SMA 2 Bandung. To achieve this goal, this study uses a qualitative descriptive research type. Data collection techniques are carried out through, Observation, interviews, and documentation—determination of informants using a purposive sampling technique. Furthermore, data analysis was carried out using descriptive analysis and data validity techniques using data triangulation. The results of the study concluded that the efforts made by Islamic religious teachers included reading the asmaul husna routinely, tadarus and praying before starting learning, midday prayers in congregation, Duha prayers, Friday prayers, with the routine commemoration of Islamic holidays (PHBI), namely commemorating Maulid Nabi, Isro Mi'raj, Islamic New Year, Eid al-Qurban, Smartren (Ramadan boarding school), and social services.